Empowering Green Mobility: The Role Of Semiconductors On The Diffusion Of Electric Vehicles In India (International Journal of Environmental Sciences, 2025)
This research examines the crucial role of semiconductor availability on accelerating diffusion of electric vehicle (EV) in Indian market. It examines how the semiconductor availability influences other manufacturing side EV diffusion barriers, including battery technology, motor technology, charging infrastructure, charging time, and battery life. Through the application of DEMATEL methodology, semiconductors availability is identified as a primary barrier affecting others, while expert feedback using the Delphi method confirms that limited semiconductor availability is a most influential barrier in EV manufacturing. The study advocates for developing a robust domestic semiconductor ecosystem that incorporates improved infrastructure, financial incentives, and strengthened collaboration between public and private sectors. Furthermore, it stresses the importance of international partnerships to enable technology transfer and fast-track skill development, thereby attracting foreign direct investments. These efforts are essential to mitigate supply chain disruptions and enhance semiconductor availability. Considering India’s ambitious goals for EV expansion, addressing the semiconductor shortage is imperative to overcome structural challenges such as high vehicle costs, insufficient charging facilities, and heavy reliance on imports. By presenting practical policy recommendations, this research highlights the essential role of semiconductors in driving EV diffusion, providing a strategic roadmap to reduce barriers, stimulate industry growth, and promote environmental sustainability in India.